Employee satisfaction and environmental reputation - Sulkowski, Adam; Walsh, Casssandra (Ökologisches Wirtschaften - Fachzeitschrift, 2011)
Companies around the world are investing in both reducing their negative environmental impacts and in communication efforts to improve their reputation for being green. Scholars, managers, and others have been trying to determine the effects of such investments.